Improvement of technical education in public technical secondary schools (Ecole Technique Officiel - ETOS) in Rwanda - Maringa, Maina (Penerbit UTHM, 2010)
This paper presents a brief review of the state of technical education in Rwanda based on a study conducted in 2007, with pertinent recommendations. The background of technical education in the country is appreciated first, and then followed up with a situational analysis. Thereafter, a 5-year implementation project plan proposal, to address the identified shortcomings, needs, and expectations of government is advanced. The need to raise access to post tronc commun (post O-Level) technical training is addressed within this proposal with a specific interest to increase the capacity and range of programmes running in the existing ETOs, and the introduction of new ETOs where deemed necessary. The establishment and sustenance of a good quality technical education system is also given consideration in this proposal for effective and efficient rehabilitation of existing physical facilities and the purchase of new and appropriate training equipment. Simultaneously, considerations for increasing the number of technical teachers in the system to a determined optimum level while setting minimum acceptable qualifications for technical teachers are advanced. Implementation of this proposal is expected to contribute greatly to the continuous development of a labour pool with skills that are relevant to and adequate for the needs of the economy.